Effect of Dupilumab on Allergen-Specific IgE Levels and Clinical Tolerance in Patients with Food Allergy: A Systematic Review - Magdalena Grześk-Kaczyńska; Szymon Kaczyński; Bernadetta Kosztulska; Magdalena Rydzyńska; Tomasz Rosada; Natalia Ukleja-Sokołowska (International Journal of Molecular Sciences, 2026)
Food allergy is a growing global health concern associated with significant dietary restrictions, impaired quality of life, and risk of severe allergic reactions. Dupilumab, a monoclonal antibody targeting the interleukin-4 receptor alpha (IL-4Rα), inhibits IL-4 and IL-13 signaling and has demonstrated efficacy across multiple type 2 inflammatory diseases. This systematic review aimed to evaluate the effects of dupilumab on food allergy outcomes in pediatric and adult patients. Across studies, dupilumab treatment was consistently associated with reductions in total immunoglobulin E (IgE) and food-specific IgE levels, indicating modulation of allergic sensitization and type 2 inflammation. However, these immunologic improvements were not consistently accompanied by clinically meaningful desensitization or acquisition of food tolerance. In a phase II trial of peanut allergy, dupilumab monotherapy reduced immunologic markers but did not improve oral food challenge outcomes. When combined with oral immunotherapy, dupilumab modestly enhanced desensitization rates but did not substantially reduce treatment-related allergic reactions. Current evidence suggests that dupilumab favorably affects immunologic markers associated with food allergy, particularly total and allergen-specific IgE levels. Nevertheless, there is insufficient evidence to conclude that dupilumab alone induces sustained clinical tolerance to food allergens. Larger randomized controlled trials incorporating standardized oral food challenges and long-term follow-up are required to clarify the clinical role of dupilumab in food allergy management.